1999
DOI: 10.1080/026520399283669
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposures to nitrate in the UK

Abstract: Dietary exposures to nitrate have been estimated for two different groups of UK consumers. The daily dietary exposure of the general population was estimated from the UK 1997 Total Diet study to be 52 mg/day. Vegetables contributed approximately 70% to this total dietary exposure. Dietary exposure estimates for adult consumers of vegetables commonly eaten in the UK were 93 mg/day and 140 mg/day for mean and 97.5th percentile consumers, respectively. Dietary exposures to nitrate of UK consumers are similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 20 publications
1
74
0
Order By: Relevance
“…The median nitrate intake of the athletes in the current study (106 mg/d) falls within the upper range of previous findings in the general population. Furthermore, similar to what has been reported for the general population (Petersen& Stoltze, 1999;Ysart et al, 1999), we found great interindividual variation in the nitrate intake of athletes (19-525 mg/d).…”
Section: Discussionsupporting
confidence: 73%
“…The median nitrate intake of the athletes in the current study (106 mg/d) falls within the upper range of previous findings in the general population. Furthermore, similar to what has been reported for the general population (Petersen& Stoltze, 1999;Ysart et al, 1999), we found great interindividual variation in the nitrate intake of athletes (19-525 mg/d).…”
Section: Discussionsupporting
confidence: 73%
“…Foodstuffs contain varying concentrations of NO 3 -, with leafy vegetables and beetroot (BR) a relatively rich source [7]. The awareness and consumption of NO 3 -has been enhanced by the recent commercialisation of BR, chard and rhubarb concentrates in products such as Beet it® (James White Drinks) and Go+Nitrate® gel (Science in Sport).…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 99%
“…Vegetable consumption accounts for 60-80% of dietary NO 3 -intake [10] with leafy-green vegetables (e.g., spinach and lettuce varieties) and beetroot being particularly rich in NO 3 - [7]. It has been reported that consuming 5 portions of NO 3 --rich vegetables for 7 days, which provided a daily NO 3 -intake of ~ 317 mg (5.1 mmol), lowered systolic blood pressure, whereas a control diet where participants avoided NO 3 --rich vegetables, resulting in a daily NO 3 -intake of ~ 8 mg (0.1 mmol), did not [9].…”
Section: Introductionmentioning
confidence: 99%